Positronium interaction and its Bose-Einstein condensation - Adhikari, Sadhan Kumar [UNESP] (Wiley-v C H Verlag Gmbh, 2009)
We present the actual state of affairs and future perspectives in the study of a quantum system of a collection of positronium (Ps) atoms. The interaction of a Ps atom with other atoms and molecules and specially with another Ps atom is described in some detail as Ps-Ps interaction should play a crucial role in the dynamics of an assembly of Ps atoms. Using a simple model-exchange potential, we could describe the available experimental results of Ps scattering reasonably well. The present scenario of the observation of Ps2 molecule, Ps Bose-Einstein condensate (BEC) and the annihilation laser from a Ps BEC is presented. Possibilities of a Ps BEC formation via laser cooling of Ps atoms and via Ps formation in cavities are considered and difficulties with each procedure discussed (C) 2009 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim